PENINGKATAN KETRAMPILAN PIJAT OKSITOSIN PADA KADER DI WILAYAH POSYANDU MELATI RT 04 RW 06 KEL. TASIKMADU, KEC. LOWOKWARU, KOTA MALANG - Yuliyanik, Yuliyanik (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2018)
Oxytocin massage also makes mothers more comfortable in breastfeeding babies. Situation analysis obtained from community service partners at Posyandu Melati RT 04 RW 06 KelurahanTasikmadu in Lowokwaru District, Malang City is that posyandu cadres do not know about oxytocin massage and the benefits of oxytocin massage. This is due to a lack of understanding of the importance of oxytocin massage and the lack of knowledge about oxytocin massage. The solution offered by the Community Service implementation team is counseling and practice to cadres about oxytocin massage and has been carried out by the implementing team. The results and outcomes that we got in this activity were the improvements of Posyandu Melati cadre skills RT 04 RW 06 Tasikmadu Kel. Lowokwaru Kec. Malang City about oxytocin massage to help the mother to make her milk smooth, mother also felt comfortable.